ANALYSIS OF KIDNEY HISTOPATHOLOGY IN SEPSIS MODEL OF MICE (MUS MUSCULUS) WITH PREVENTIVE TREATMENT OF LEAF EXTRACT FROM 'DAUN KENTUT' PLANT (PAEDERIA FOETIDA L.) AGAINST ESCHERICHIA COLI INFECTION - Lisa Savitri; Elfred Rinaldo Kasimo; Rochmad Krissanjaya; Datin An Nisa Sukmawati; Syntia Tanu Juwita; Akbar Nur Kholis; Yosep Mosse1 (Jurnal Bioteknologi dan Biosains Indonesia, 2023)
Sepsis is a critical health concern characterized by organ dysfunction due to uncontrolled host reactions to infections. The prevalence of microorganisms causing sepsis varies, with Gram-positive bacteria and fungal sepsis gaining significance. Sepsis often leads to acute kidney injury (AKI), and its association with sepsis is known as sepsis-associated AKI (SA-AKI). The "Daun Kentut" plant, known for its diverse bioactive compounds, has shown potential in combating inflammation and oxidative stress. In this study, histopathological changes in mouse kidneys induced by Escherichia coli were investigated. Hemorrhage was the primary change observed. Dehydration caused by E. coli infection potentially led to kidney injury through hormonal responses. The plant extract's anti-inflammatory potential, attributed to compounds like saponins and flavonoids, was also explored. The study emphasizes the need for understanding sepsis-related kidney damage and suggests possible preventive strategies using natural compounds.